Hubungan Dukungan Keluarga Dengan Motivasi Mengikuti Vaksinasi Covid-19 - Lono Wijayanti; Riska Rohmawati; Rahayu Anggraini; Siti Damawiyah (Jurnal Keperawatan Muhammadiyah, 2022)
Background: Covid-19 has infected a lot of people in various countries. The implementation of vaccination raises new problems in the public, there are positive and negative reactions regarding the vaccination program. Incorrect data regarding the Covid-19 vaccine causes anxiety, fear and doubt.Objective: The purpose of this study was to determine the relationship between family support and motivation to participate in Covid-19 vaccination among members of Tentara Nasional Indonesia (TNI) Angkatan laut (AL) in the Kodiklatal Satkes area.Method: This research used a correlational analytic design with a cross sectional approach. The population in this research is all members of the Tentara Nasional Indonesia (TNI) Angkatan laut (AL) with the rank of enlisted in the Kodiklatal Satkes area as many as 384 people. The sample is 196 respondents using simple random sampling. The independent variable is family support and the dependent variable is motivation to participate in the Covid-19 vaccination.Results: The results showed that of the 196 respondents, most (58.7%) had good family support and most (52.8%) had high motivation. Based on the Spearman rank test, p value = 0.000 (p <0.05) which means that there is a significant relationship between family support and motivation to participate in the Covid-19 vaccination for members of the Tentara Nasional Indonesia (TNI) Angkatan laut (AL) with the rank of enlisted in the Kodiklatal Satkes area.Conclusion: The better the family support, the higher the motivation of a person in participating in the implementation of vaccination. It is hoped that regular guidance from health facilities and health workers can increase one's motivation in participating in the implementation of the Covid-19 vaccination.